Integrating civic education and student management development: how come? - Nuphanudin , Nuphanudin; Wardani, Helda Kusuma; Gmaliel, F.X.; Pattipeilohy, Poltjes; Ansori, Aristawidya Salsabila (Jurnal Indovisi, 2024)
This study explores how civic education can be effectively integrated with student management development in higher education through an information diffusion framework. The main objective of the study is to examine how the processes of acceptance, control, and dissemination influence the development of civic education and student leadership. Civic education is not only viewed as a formal subject, but also as a broader educational practice embedded within student management and institutional culture. A qualitative descriptive approach was employed to capture real experiences and perspectives related to civic education practices. The participants were students enrolled in civic education related courses in a higher education setting. Data were collected through in depth interviews, observations, and documentation to obtain a comprehensive understanding of how civic values and leadership skills are developed. The collected data were analyzed using the Miles and Huberman interactive model, which consists of data condensation, data display, and conclusion drawing or verification. The findings indicate that the diffusion of information across the acceptance, control, and dissemination levels plays a significant role in shaping students’ civic awareness and leadership development. Acceptance enables students to internalize civic values, control ensures consistency and guidance in educational practices, and dissemination supports the broader spread of civic knowledge and leadership norms within the academic environment. These interconnected processes contribute to a more effective integration of civic education and student management. This study highlights the importance of adopting a systematic and integrated approach to civic education in higher education institutions. The findings provide practical insights for educators and policymakers in designing programs that strengthen civic education and student leadership, and offer a conceptual foundation for future research on information diffusion and civic education development.